2002
DOI: 10.1093/emboj/21.7.1514
|View full text |Cite
|
Sign up to set email alerts
|

The novel product of a five-exon stargazin-related gene abolishes CaV2.2 calcium channel expression

Abstract: contributed equally to this workWe have cloned and characterized a new member of the voltage-dependent Ca 2+ channel g subunit family, with a novel gene structure and striking properties. Unlike the genes of other potential g subunits identi®ed by their homology to the stargazin gene, CACNG7 is a ®ve-, and not four-exon gene whose mRNA encodes a protein we have designated g 7 . Expression of human g 7 has been localized speci®cally to brain. N-type current through Ca V 2.2 channels was almost abolished when co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
73
1
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 36 publications
3
73
1
1
Order By: Relevance
“…One previously characterized role of Stargazin and related proteins in calcium channel modulation is their inhibitory effect on current amplitude and expression of the channels. 7,9,10 In accordance with the above reports, our study showed that coexpression of Stargazin with the Ca V 2.2 channel inhibited current amplitudes, and coexpression of Stargazin and Ca V 2.2 containing YFPtagged α 1B subunit (YFP-α 1B ), decreased channel surface expression. This inhibitory effect seemed independent of Gβγ, as Stargazin decreased channel expression in oocytes with or without coexpressed Gβγ.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…One previously characterized role of Stargazin and related proteins in calcium channel modulation is their inhibitory effect on current amplitude and expression of the channels. 7,9,10 In accordance with the above reports, our study showed that coexpression of Stargazin with the Ca V 2.2 channel inhibited current amplitudes, and coexpression of Stargazin and Ca V 2.2 containing YFPtagged α 1B subunit (YFP-α 1B ), decreased channel surface expression. This inhibitory effect seemed independent of Gβγ, as Stargazin decreased channel expression in oocytes with or without coexpressed Gβγ.…”
supporting
confidence: 91%
“…[5][6][7] Later studies revealed that Stargazin is a crucial regulator of AMPA receptors. 8 Still, Stargazin and other γ proteins were found to inhibit calcium channel currents and expression, 9,10 while their effect on channel's biophysical properties remained debated. 7,9,[11][12][13][14] We have recently discovered that Stargazin modulation of Ca V 2.2 channels coexpressed in Xenopus oocytes is dependent on the G protein βγ subunit.…”
mentioning
confidence: 99%
“…In the recent past, a number of ␥ subunits that are expressed in a variety of tissues have been cloned (13)(14)(15)(16), and their functional roles are only beginning to be revealed. In general, the ␥ subunits appear to be inhibitory (7,22,30,34). The important physiological role for the ␥ subunit is emphasized by the epileptic phenotype in the stargazer mouse, a spontaneous mutant that lacks the ␥ 2 subunit (13).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that ␥-5 does not modulate AMPA receptor function in oocytes (Tomita et al, 2004). And, a preliminary characterization suggested that ␥-7 can inhibit the expression of calcium channels in oocytes or transfected cells (Moss et al, 2002). Here, we explored functional roles for ␥-5 and ␥-7 proteins, which unexpectedly define ␥-7 as a new member of the TARP family that differentially regulates AMPA receptors.…”
Section: Introductionmentioning
confidence: 92%